Assessment of sleep quality and its association with problematic internet use among university students: a cross-sectional investigation in Bangladesh - Islam, Zohurul; Hsan, Kamrul; Islam, Saiful; Gozal, David; Hossain, Mahfuz (Sleep Science, 2021)
Objectives: Problematic internet use (PIU) is a major behavioral problem that has been closely associated with poor sleep quality in many different countries, but is poorly studied in Bangladesh. This study was conducted to investigate the sleep quality and its association with PIU among university students in Bangladesh.Material and Methods: A cross-sectional study was conducted between May 2019 and December 2019 among 400 students attending four public universities in Bangladesh. The Pittsburgh sleep quality index (PSQI) was used to determine sleep quality and Young’s internet addiction test (IAT) was used to describe the degree of PIU.Results: A significant negative association emerged between good sleep quality and PIU (p<0.001). In the multivariate logistic regression, students having PIU were 0.28 folds less likely to have good sleep quality (AOR: 0.28, 95%CI=0.18-0.43, p<0.001) when compared to non-PIU students. In addition, significant associations between sleep quality and socio-demographic and lifestyle factors were identified.Conclusion: Implementation of an effective awareness program and development of education strategies are required to reduce internet addictive behaviors and improve sleep quality among Bangladeshi university students.
Keywords: Sleep Quality; Problematic Internet Use; Internet Addiction; University Students; Bangladesh